3(c+2)c+1=57

Simple and best practice solution for 3(c+2)c+1=57 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(c+2)c+1=57 equation:



3(c+2)c+1=57
We move all terms to the left:
3(c+2)c+1-(57)=0
We add all the numbers together, and all the variables
3(c+2)c-56=0
We multiply parentheses
3c^2+6c-56=0
a = 3; b = 6; c = -56;
Δ = b2-4ac
Δ = 62-4·3·(-56)
Δ = 708
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$c_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$c_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{708}=\sqrt{4*177}=\sqrt{4}*\sqrt{177}=2\sqrt{177}$
$c_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(6)-2\sqrt{177}}{2*3}=\frac{-6-2\sqrt{177}}{6} $
$c_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(6)+2\sqrt{177}}{2*3}=\frac{-6+2\sqrt{177}}{6} $

See similar equations:

| 40-x=4(-3+-6x)+6 | | -3k+-4.3=-1.3 | | 7r+5=10 | | 2x=48+x | | c/3-1.5=1.9 | | u/5=11/8 | | d/6-17=6 | | 9+7y=-5 | | 1.2(3k-2.5)+7.2k=19.68 | | x^3+8x^2+15=0 | | s/6-5=13 | | 18=-6(1-1k) | | 14x+-26=16 | | 8c-11=205 | | 5+1/7b=-3 | | 15u=18=18 | | 9x+57=15 | | 4x+5=7x+13 | | q/12-(-284)=299 | | 6(-8+3b)=78 | | 3(2x-8)-7=-61 | | 2/3e=-14 | | |-8p|=72 | | -12=6m+4 | | x/20-10=-6 | | -2x/3-7/3=-2 | | .333333333(9-2x)=x+1 | | 5n^2+86=0 | | 10x+8=3x+50 | | 27v-55=566 | | 3/4x+1/2x+5/6=3/8 | | 27(c-948)=432 |

Equations solver categories